2016
DOI: 10.1016/j.euroneuro.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Mouse psychosocial stress reduces motivation and cognitive function in operant reward tests: A model for reward pathology with effects of agomelatine

Abstract: A major domain of depression is decreased motivation for reward. Translational automated tests can be applied in humans and animals to study operant reward behaviour, aetio-pathophysiology underlying deficits therein, and effects of antidepressant treatment. Three inter-related experiments were conducted to investigate depression-relevant effects of chronic psychosocial stress on operant behaviour in mice. (A) Non-manipulated mice were trained on a complex reversal learning (CRL) test with sucrose reinforcemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 55 publications
8
35
1
Order By: Relevance
“…The present results are consistent with a recent study where defeated mice underperformed on PR tests for sucrose pellets following chronic social defeat (Bergamini et al 2016). However, the results differ from a report that social defeat led to persistent increases in operant performance for sucrose solution on a PR schedule (Riga et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The present results are consistent with a recent study where defeated mice underperformed on PR tests for sucrose pellets following chronic social defeat (Bergamini et al 2016). However, the results differ from a report that social defeat led to persistent increases in operant performance for sucrose solution on a PR schedule (Riga et al 2015).…”
Section: Discussionsupporting
confidence: 93%
“…The nucleus accumbens regulates motivation in mammals (Da Cunha et al, 2012), is essential for rearing (Lever et al, 2006), and CSD induces spine morphology alterations and increased synaptic transmission 20/38 amongst medium spiny inhibitory neurons in this area (Christoffel et al, 2011). In addition, we have demonstrated that CSD and dopamine depletion in the nucleus accumbens both lead to reduced motivation to obtain food reward under effortful conditions (Bergamini et al, 2016). These findings and others have made the nucleus accumbens a new potential target area to treat MDD through deep-brain stimulation (Nauczyciel et al, 2013), and raise the possibility that structural modifications within the nucleus accumbens, potentially instigated from hippocampo-amygdalar signalling, underlie the blunted drive to explore observed in this study.…”
Section: Csd Mdd and Exploratory Drivementioning
confidence: 81%
“…There is therefore only a limited theoretical framework and narrow selection of tools currently available to probe the mechanisms underlying loss of exploratory drive in mental illness (Der-Avakian & Markou, 2012;Calabrese et al, 2014;Hershenberg et al, 2016). Given this minimal examination, and since better understanding exploration deficits could yield novel targets 6/38 and strategies for treating mental illness, we examined exploratory behaviours in mice following chronic social defeat (CSD), a social manipulation that induces pathophysiology reminiscent of MDD (Krishnan et al, 2007;Yan et al, 2010;Azzinnari et al, 2014;Fuertig et al, 2015;Grandjean et al, 2016;Bergamini et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…CSS leads to reduced reward-directed behavior, 40,41 increased aversion learning, helplessness and fatigue, 38,42,43 increased fMRI restingstate functional connectivity within PFC and between PFC and amygdala, 44 increased amygdala inositol levels 44 and increased immune/inflammatory activation in periphery and amygdala and PFC. 38,41,42 Utilizing this depression-relevant model, the present study shows that CSS in mice leads to reduced expression of a number of oligodendrocyte genes in PFC and amygdala tissue comprising gray and white matter.…”
Section: Discussionmentioning
confidence: 99%